2019
DOI: 10.1111/1475-4932.12504
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Energy‐related Financial Stress in Australia

Abstract: This paper quantifies factors affecting energy‐related financial stress in Australia, a key economic challenge facing a minority of households. We find that low net wealth is a particularly important factor affecting difficulty in paying energy bills. Having insulation reduces reported difficulties in being able to heat and cool homes. The odds of not paying energy bills on time are doubled by households not having solar panels. Other important factors contributing to energy‐related financial stress include be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…For example, there could be a boost to the Age Pension rate or other payments such as through higher Commonwealth Rent Assistance (Coates, 2018) or through higher payments for disability pensioners. Targeting renters, including female renters, could be effective as they tend to be more at risk of dimensions of poverty and financial stress (Austen, 2016; Best & Burke, 2019). Additional targeting may be necessary as there may be constraints on general level increases for all pension recipients.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…For example, there could be a boost to the Age Pension rate or other payments such as through higher Commonwealth Rent Assistance (Coates, 2018) or through higher payments for disability pensioners. Targeting renters, including female renters, could be effective as they tend to be more at risk of dimensions of poverty and financial stress (Austen, 2016; Best & Burke, 2019). Additional targeting may be necessary as there may be constraints on general level increases for all pension recipients.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Potential negative rebound effects on electricity consumption driven by the desire of vulnerable households to catch up with middle-class living standards could be counterbalanced by positive health and social benefits [99,100]. Recent studies have found that the psychological stress caused by the inability to pay energy bills and the fear of debt, which triggers feelings of anxiety and depression, can be a consequence of energy vulnerability [101] and can contribute to and shape it [102].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we contribute to the nascent literature on the behavioural and environmental reasons why some people exhibit a higher likelihood of being in energy poverty. Traditionally, most research on the causes of energy poverty has focused on the roles of high energy prices, low income, energy inefficient housing and energy inefficient home appliances (Best & Burke, 2019;Legendre & Ricci, 2015;Moore, 2012). While these studies have helped characterize whether people live in energy poverty, they do not tell us why one has low income and/or has high energy bills.…”
Section: Introductionmentioning
confidence: 99%